(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role of digital technologies in fostering creative and critical thinking among academic lyceum students in the context of geometry education. The study emphasizes that traditional methods of teaching geometry often fail to fully develop spatial imagination and logical reasoning, while digital tools provide dynamic, interactive, and visual learning opportunities.